2018
DOI: 10.1152/japplphysiol.00174.2018
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular and skeletal muscle health with lifelong exercise

Abstract: The purpose of this study was to examine the effects of lifelong aerobic exercise (LLE) on VOmax and skeletal muscle metabolic fitness in trained females (n=7, 72±2y) and males (n=21, 74±1y), and compare them to old healthy non-exercisers (OH; females: n=10, 75±1y; males: n=10, 75±1y), and young exercisers (YE; females: n=10, 25±1y; males: n=10, 25±1y). LLE males were further subdivided based on intensity of lifelong exercise and competitive status into performance (LLE-P, n=14) and fitness (LLE-F, n=7). On av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
87
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(100 citation statements)
references
References 58 publications
11
87
0
2
Order By: Relevance
“…Nevertheless, it is clear from our results that chronic endurance exercise training leads to greater MHC I and II fibre capilliarisation in MA compared with OC and, in some cases, YC. These findings are consistent with recent evidence that the continuation of endurance training into older age maintains skeletal muscle capilliarisation47 .However, recent evidence from a cross-sectional analysis of highly trained MA (55-79 y)suggests that chronic endurance training does not completely prevent the decline in capillary density12 . Nevertheless, the greater muscle fibre capilliarisation and MHC I fibre area observed in our cohort of endurance-trained MA may, at least partly, explain their superior aerobic fitness levels.Whilst our findings clearly demonstrate superior indices of physiological function and muscle morphology in MA compared with OC, we are unable to determine whether chronic endurance exercise offsets the trajectory of age-related physiological deterioration.…”
supporting
confidence: 89%
“…Nevertheless, it is clear from our results that chronic endurance exercise training leads to greater MHC I and II fibre capilliarisation in MA compared with OC and, in some cases, YC. These findings are consistent with recent evidence that the continuation of endurance training into older age maintains skeletal muscle capilliarisation47 .However, recent evidence from a cross-sectional analysis of highly trained MA (55-79 y)suggests that chronic endurance training does not completely prevent the decline in capillary density12 . Nevertheless, the greater muscle fibre capilliarisation and MHC I fibre area observed in our cohort of endurance-trained MA may, at least partly, explain their superior aerobic fitness levels.Whilst our findings clearly demonstrate superior indices of physiological function and muscle morphology in MA compared with OC, we are unable to determine whether chronic endurance exercise offsets the trajectory of age-related physiological deterioration.…”
supporting
confidence: 89%
“…Prior research has found that that sedentary elderly subjects have ~25% lower capillarization than sedentary young subjects, while elderly master athletes (i.e. lifelong exercisers) have similar capillarization to young athletes [50][51][52] ; we find a similar pattern in endothelial cell compartment changes with training. Although there is little data regarding levels of immune cells in skeletal muscle during the menstrual-cycle, there are menstrual-cycle related differences in the proportions of circulating immune cell types 53 .…”
Section: Discussionsupporting
confidence: 67%
“…All procedures associated with the research were approved by the Institutional Review Board at Ball State University and performed in accordance with relevant guidelines and regulations. Subjects 8,52 provided written informed consent prior to participation. Muscle biopsies were obtained from the vastus lateralis as we have previously described 8,52 .…”
Section: Methodsmentioning
confidence: 99%
“…Similar to Section 4.1, we successively consider the cases where the coupling constraint in (P × ′ ) is loose or tight. In both cases, we will show that the optimal practice process can be structured in cycles, demonstrating the power of habit for skill retention, consistent with the empirical evidence of the benefits of lifelong exercise (Gries et al 2018).…”
Section: Multiplicative Model (Skill Retention)supporting
confidence: 77%
“…In addition to developing mathematical models, the physiology literature provides ample evidence of high-performance strategies such as "tapering" (i.e., progressively reducing the training load before a race [Mujika and Padilla 2003]), "periodization" (i.e., structuring the training program in cycles of highintensity sessions followed by periods of recovery [Bompa and Haff 2009]), and lifelong exercise for long-term benefits (Gries et al 2018). However, few attempts have been made to demonstrate the optimality of such strategies besides Morton (1991) and Banister et al (1999), who evaluated the performance of a specific set of training profiles via simulation.…”
Section: Training For Endurance Sportsmentioning
confidence: 99%